Analisis Kebutuhan dan Ketersediaan Air Bersih Kelurahan Lakkang Kota Makassar - Riosetiawan, Andi Ahmad; Syahrir, Suryani; Yusuf, Andi Rumpang (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Clean water is a natural resource that is very important and vital for human life. By providing good clean water, it will support the improvement of people's health and welfare. The aim of this research is to analyze the total need and availability of clean water as well as reservoir capacity requirements. This research was conducted in Lakkang Village, Makassar City. In this research, the method used is quantitative descriptive, a study to determine the need for clean water, as well as reviewing the availability of water sources and the required reservoir capacity. Data analysis includes predictions of population, predictions of increase in PDAM customers as well as predictions of reservoir capacity. The results of the analysis state that the total need for clean water is 0,2434 liters/person/second and the availability of clean water is 1300 liters/second and the required reservoir capacity is 5,05 m3, which is smaller than the current capacity of 8 m3. The need and availability of clean water is still sufficient and reservoir capacity is still adequate in Lakkang Village, Makassar City until 2027.